1986
DOI: 10.1002/cne.902520304
|View full text |Cite
|
Sign up to set email alerts
|

Cortical connections of the somatosensory fields of the lateral sulcus of macaques: Evidence for a corticolimbic pathway for touch

Abstract: The ipsilateral corticocortical connections of the somatosensory fields of the lateral sulcus of macaques were examined with both anterograde and retrograde axonal transport methods. In most cases, the field of interest was identified prior to the injection of the tracer substance by recording neuronal responses to somatic stimulation. The results show that the second somatosensory area (S2) is reciprocally connected with the retroinsular area (Ri), area 7b, and the granular (Ig) and dysgranular (Id) insular f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
294
2
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(329 citation statements)
references
References 72 publications
25
294
2
3
Order By: Relevance
“…In this model, neurons that have partially invariant (ID and IC) or strongly locally tuned responses provide feedforward, convergent input to neurons that show invariance across the entire finger pad. Another possibility, which is not mutually exclusive, is that the convergent inputs for all of the tuned SII region neurons come from lower-order somatosensory neurons in SI that project to the SII region (Friedman et al, 1980(Friedman et al, , 1986Pons et al, 1987Pons et al, , 1992Burton et al, 1995;Disbrow et al, 2003). Previous studies have shown that many of the RFs in SI show approximately linear response properties and have approximately circular or slightly elongated lobes of excitation or inhibition, like most of the D, C, and DC neurons we report here (DiCarlo et al, 1998;Sripati et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In this model, neurons that have partially invariant (ID and IC) or strongly locally tuned responses provide feedforward, convergent input to neurons that show invariance across the entire finger pad. Another possibility, which is not mutually exclusive, is that the convergent inputs for all of the tuned SII region neurons come from lower-order somatosensory neurons in SI that project to the SII region (Friedman et al, 1980(Friedman et al, , 1986Pons et al, 1987Pons et al, , 1992Burton et al, 1995;Disbrow et al, 2003). Previous studies have shown that many of the RFs in SI show approximately linear response properties and have approximately circular or slightly elongated lobes of excitation or inhibition, like most of the D, C, and DC neurons we report here (DiCarlo et al, 1998;Sripati et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a cortico-limbic pathway has been described to pass from the primary and secondary somatosensory cortices to insular and parietal cortical structures, then to the amygdala, the perirhinal cortex and the hippocampus, and ultimately converges on the same structures that are directly activated by the spinothalamic pathways [64,65] . This pathway integrates sensory pain characteristics with information from other sensory systems as well as learning and memory, thus adding a cognitive aspect regarding long-term consequences to affective pain processing [66,67] .…”
Section: Cortico-limbic Pathwaymentioning
confidence: 99%
“…According to this corticolimbic pathway, an indirect route for pain signals into the HF is naturally expected: the interaction or crosstalk between the lateral and medial system [66] . To note, the insula is one critical region in this cortico-limbic pathway and the efferents from the insula supply the HF via its projection to the parahippocampal region, among which is the EC [64,65] .…”
Section: Cortico-limbic Pathwaymentioning
confidence: 99%
“…In the somatosensory system, previous studies have suggested that information from multiple lower-order somatosensory cortical areas converges onto a single representation in the SII region (Friedman et al, 1986;Hsiao et al, 2003). Our current finding that the SII region contains three fields with distinct functional properties suggests that multiple distributed hierarchical processing streams also exist in the somatosensory system.…”
Section: Functional Significancementioning
confidence: 99%